Differentiation of functionally active mouse T lymphocytes from functionally inactive bone marrow precursors. III. Induction of T-cell activities by growth of bone marrow on feeder layers prepared from mouse thymocytes. - Gorczynski, R M (1979)
The ability of small and large T precursor cell pools to differentiate into mature functional T lymphocytes on thymus feeder cell layers or in the presence of a supernatant prepared from such feeder layers was compared. Evidence was obtained showing that the small cell pool differentiated as effectively in the presence of soluble factors prepared from the thymus cultures as in the presence of the thymus cells themselves. In contrast, large stem cells apparently needed cellular contact with the thymus feeder cultures in order to promote differentiation, though a time point could be found at which further differentiation from this precursor pool would also occur in the presence of the thymus culture supernatant only. These data concurred with evidence from in vivo experiments for two pools of T-cell precursors which differentiated in thymectomized or thymus-intact recipients respectively.